Nilai Perusahaan : Dampak dari Return On Asset (ROA), Return On Equity (ROE) dan Corporate Social Responsibility (CSR) - Diah Retno Sulistiyowati; Anita Syafariah (Prodi Manajemen S1 dan D3 Keuangan & Perbankan, 2019)
This study aims to examine the effect of Return on Assets (ROA), Return on Equity (ROE) and Corporate Social Responsibility (CSR) on firm value. The research method used is descriptive and associative. The population and sample used are all telecommunications companies listed on the Indonesia Stock Exchange (IDX). The analysis technique used is multiple linear regression analysis. Based on the results of the study indicate that Return on Assets (ROA) has a significant positive effect on firm value (P <0.05). Return on Equity (ROE) does not have a significant effect on firm value (P> 0.05). Corporate Social Responsibility (CSR) has no significant effect on firm value (P> 0.05). It is suggested for the next researcher that the company studied not only in the telecommunications sector, but all companies listed on the IDX that have good characteristics to be used as populations, and are advised to examine other financial variables that affect the value of the company.